PENGARUH BAHASA ALAY TERHADAP PENGGUNAAN BAHASA INDONESIA DI KALANGAN MAHASISWA IKIP SILIWANGI - Laelasari, Laelasari; Oktavia, Lusi; Mustika, Ika (IKIP Siliwangi, 2018)
This research is triggered by the more the use of language Alay among teenagers in particular the rise of the student research aims 1) the use of language in student ikip siliwangi, and 2) to know the impact of the use of language Alay among students siliwangi. the technique of data collection benupa questionnaire respondents in the language Alay is students siliwangi a number of 30. the results showed 1) daily among students IKIP Siliwangi used used in communicaton activities language good with friends Seb or by the environment, and 2) the impact of the use of Alay among students, berpengruh to the use of Indonesian, of which students less familiar with standard language, and students less understand the use of spelling the right.